2008
DOI: 10.1080/13506280701269318
|View full text |Cite
|
Sign up to set email alerts
|

How do eye gaze and facial expression interact?

Abstract: Previous research has demonstrated an interaction between eye gaze and selected facial emotional expressions, whereby the perception of anger and happiness is impaired when the eyes are horizontally averted within a face, but the perception of fear and sadness is enhanced under the same conditions. The current study reexamined these claims over six experiments. In the first three experiments, the categorization of happy and sad expressions (Experiments 1 and 2) and angry and fearful expressions (Experiment 3) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

14
107
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(127 citation statements)
references
References 45 publications
14
107
6
Order By: Relevance
“…In light of these findings, Adams and Kleck (2005) proposed a theory of the role of gaze direction in expression perception whereby direct gaze increases attributions of approach-oriented emotions (eg anger, happiness) while averted gaze increases attributions of avoidance-oriented emotions (eg sadness, fear). More recently, however, Bindemann et al (2008) were unable to replicate Adams and Kleck's findings. Our findings for the effects of head orientation on the perceived intensity of facial expressions of emotion are also difficult to reconcile with Adams and Kleck's proposal; we found that front views of faces were perceived as showing more intense emotions than three-quarter views of faces regardless of whether subjects were judging how happy faces displaying the approach-oriented emotion happiness appeared to be or were judging how disgusted faces showing the avoidance-oriented emotion disgust appeared to be.…”
Section: Discussioncontrasting
confidence: 37%
See 1 more Smart Citation
“…In light of these findings, Adams and Kleck (2005) proposed a theory of the role of gaze direction in expression perception whereby direct gaze increases attributions of approach-oriented emotions (eg anger, happiness) while averted gaze increases attributions of avoidance-oriented emotions (eg sadness, fear). More recently, however, Bindemann et al (2008) were unable to replicate Adams and Kleck's findings. Our findings for the effects of head orientation on the perceived intensity of facial expressions of emotion are also difficult to reconcile with Adams and Kleck's proposal; we found that front views of faces were perceived as showing more intense emotions than three-quarter views of faces regardless of whether subjects were judging how happy faces displaying the approach-oriented emotion happiness appeared to be or were judging how disgusted faces showing the avoidance-oriented emotion disgust appeared to be.…”
Section: Discussioncontrasting
confidence: 37%
“…Our findings for the effects of head orientation on the perceived intensity of facial expressions of emotion are also difficult to reconcile with Adams and Kleck's proposal; we found that front views of faces were perceived as showing more intense emotions than three-quarter views of faces regardless of whether subjects were judging how happy faces displaying the approach-oriented emotion happiness appeared to be or were judging how disgusted faces showing the avoidance-oriented emotion disgust appeared to be. Like Bindemann et al (2008), we found little evidence that gaze direction has different effects on perceptions of approach-and avoidance-oriented emotions.…”
Section: Discussionmentioning
confidence: 40%
“…However, there is also evidence for cross-talk in the opposite direction: from mechanisms processing gaze to those processing expression (Adams & Kleck, 2003;Bindemann, Burton, & Langton, 2008;Ganel, Goshen-Gottstein, & Goodale, 2005). If an averted gaze could somehow reduce the salience of angry, but not happy facial expressions, then this could explain why recognition memory was poor for the identity of faces shown with angry faces and averted gaze.…”
mentioning
confidence: 99%
“…If an averted gaze could somehow reduce the salience of angry, but not happy facial expressions, then this could explain why recognition memory was poor for the identity of faces shown with angry faces and averted gaze. Unfortunately, however, the evidence suggests that gaze direction exerts equivalent effects on the processing of both happy and angry faces: categorizations of both types of expression are slower when gaze is averted than when it is direct (Adams & Kleck, 2003;Bindemann, Burton, & Langton, 2008).…”
mentioning
confidence: 99%
“…Integrating information from multiple cues of dominance (eg face shape, gaze direction) may function to increase the efficiency with which one attributes dominance to others during social interactions. Adams and Kleck (2003) have previously found that viewers were more sensitive to angry facial expressions shown with direct gaze than angry facial expressions shown with averted gaze, but also found that viewers were more sensitive to fearful expressions shown with averted gaze than fearful expressions shown with direct gaze (but see also Bindemann et al 2008). That angry faces are rated as more dominant than fearful faces (Hess et al 2000) therefore raises the possibility that viewers may also be more sensitive to physical cues of dominance (eg masculine face shape) when judging the dominance of faces with direct gaze than when judging the dominance of faces with averted gaze.…”
mentioning
confidence: 99%